Accretionary growth and crust formation in the Central Asian Orogenic Belt and comparison with the Arabian-Nubian shield - Kröner A.; Windley B.F.; Badarch G.; Tomurtogoo O.; Hegner E.; Jahn B.M.; Gruschka S.; Khain E.V.; Demoux A.; Wingate M.T.D. (My University, 2007)
The Central Asian Orogenic Belt is one of the largest accretionary terrains on Earth and records a ca. 800 Ma history of arc and microcontinent accretion, from south to north, during evolution and closure of the southwest Paciﬁ c-type Paleo-Asian ocean in the period ca. 1020 to ca. 325 Ma. We contest the evolutionary model for the belt proposed by previous authors in terms of a single, long island arc. Accretion of ophiolites, arcs, and Precambrian microcontinents took place in southern Siberia in late Neoproterozoic to Cambrian times. Ultrahigh-pressure subduction and metamorphism occurred in the Cambrian at Kokchetav, Kazakhstan, and high-pressure metamorphism took place in the Gorny Altai, together with arcward accretion of a seamount. In the Chinese Altai, Precambrian microcontinents and island arcs collided into the accreting margin.
Keywords: accretion; Arabian-Nubian shield; central Asia; Kazakhstan; Mongolia; zircon geochronology; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская